TEACHER PROFESSIONAL LEARNING IN THE PERSPECTIVE OF EDUCATIONAL TECHNOLOGY - Wawan Krismanto (Kwangsan: Jurnal Teknologi Pendidikan, 2023)
Teachers' increasingly massive and diverse use of gadgets allows their facility to be directed at teacher learning activities to improve their competence and professionalism. This research explores the professional learning of technology-based teachers from the perspective of learning technology. Apart from the fact that publication on this topic is still limited, this study is also essential as a foundation, framework, or conceptual framework for technology-based teacher professional development research. To achieve the objectives of this research, a qualitative approach through the method of literature study or library research is a research method that is considered relevant. Literature data is collected through books, literature, notes, and relevant previous research reports. The research procedure is reading, taking notes, or recording, then inventorying and processing it into research data. The research results concluded that teacher professional development shifted into professional learning. The process is conditioned and built actively, self-regulated, sustainable, and based on social and contextual processes according to the teacher's problems and needs. The learning technology perspective views that professional teacher learning not only focuses on the results of learning activities but also on processes and resources that are created, managed, and utilized optimally to facilitate various teacher learning activities through different modes or technological devices. Technology provides an opportunity to make teachers' professional learning more inclusive and sustainable. This opens up broad opportunities for future studies on technology-based teacher professional learning in the area or domain of educational technology or instructional technology.Abstrak.Penggunaan gadget yang semakin masif dan beragam oleh guru memungkinkan fasilitasnya diarahkan untuk kegiatan pembelajaran guru dalam meningkatkan kompetensi dan profesionalismenya. Penelitian ini bertujuan mengeksplorasi pembelajaran profesional guru berbasis teknologi dari perspektif teknologi pembelajaran. Selain karena publikasi tentang topik ini masih terbatas, penelitian ini juga penting sebagai landasan, kerangka, atau kerangka konseptual untuk penelitian pengembangan keprofesian guru berbasis teknologi. Untuk mencapai tujuan penelitian ini, pendekatan kualitatif melalui metode studi literatur atau studi kepustakaan merupakan metode penelitian yang dianggap relevan. Data pustaka dikumpulkan melalui buku, literatur, catatan, dan laporan penelitian sebelumnya yang relevan. Prosedur penelitiannya adalah membaca, mencatat, atau mencatat, kemudian menginventarisasi dan mengolahnya menjadi data penelitian. Hasil penelitian menyimpulkan bahwa pengembangan keprofesian guru bergeser menjadi pembelajaran profesional. Proses tersebut dikondisikan dan dibangun secara aktif, mandiri, berkesinambungan, dan berdasarkan proses sosial dan kontekstual sesuai dengan permasalahan dan kebutuhan guru. Perspektif teknologi pembelajaran memandang bahwa pembelajaran guru profesional tidak hanya terfokus pada hasil kegiatan pembelajaran tetapi juga pada proses dan sumber daya yang diciptakan, dikelola, dan dimanfaatkan secara optimal untuk memfasilitasi berbagai kegiatan belajar guru melalui berbagai moda atau perangkat teknologi. Teknologi memberikan kesempatan untuk menjadikan pembelajaran profesional guru lebih inklusif dan berkelanjutan. Ini membuka peluang luas untuk studi masa depan tentang pembelajaran profesional guru berbasis teknologi pada bidang atau domain teknologi pendidikan atau teknologi instruksional.